EVALUASI RESPON PERTUMBUHAN DAN HASIL VARIETAS JAGUNG ASAL TIMOR PADA PERBEDAAN KELAS LAHAN KERING BERBATU - Suryawati Suryawati; Aloysius Ng. Lende; Lenny M. Mooy (Partner, 2017)
Local resources isthe rocky dry land have the potential to be developed as productive land if the selection of technology and types of varieties adaptive location.  The problem is the least information abouton the nature of agronomy and the production of  adaptive local corn varieties  at rocky dryland. The study aims to: 1)  gotdata about the agronomic character of  local corn varietiesat  different class  rocky dry land. 2) obtain data about  productive corn on  rocky dry land. Experiment usingRandomizedBlock Designwith 9 replications. Treatment is 3 varieties of maize: 1) Haikesak Putih, 2) Tastim I Putih, and 3) Bunga Merah  Fatumonas. Different conditions of rocks on the surface are different locations. Criteria of a rocky dry land  class consists of Class 2: consists of  rocks that exist on the surface as much as   0.1-3.0% and the small rock is the distance  is about 1 meter. Class 3: consists of  rocks that exist on the surface as much as   3.0%-15% and the small rock is the distance  is about 0,5 meter.Class 4: consists of  rocks that exist on the surface as much as  15-25% andthe small rock is the distance  is about 0,3 meter. Observation variables consist of: 1)Growth: a) Height of plant, b) Diameter of stem, c) Width of Leaf, and 2) Production: a) Weight of maize per plant,   b) Yield per hectare.  The  research results showed   that the local corn varieties of Bunga Merah Fatumonas have the best agronomic at different class of rocky dry land.  The local corn varieties of Bunga Merah Fatumonas provide the best response to: height of plant,  weight of maize per plant,  and  yield per hectare. Key word:  Rocky dry land class, best response